The Deinstitutionalization of the Mental Hospitals and the Move to Community Mental Health Centers Focusing on Wisconsin in the 1980s - Pitman, Andrea (My University, 2009)
This paper focuses on the changes in the care and treatment of the mentally ill population in the United States. It specifically focuses on the time period between the end of World War II through the 1980s. This time period is interesting because there was a massive movement of mentally ill patients out of the mental institutions and into community based centers. This paper attempts to provide the reader with information to explain the reasons for the deinstitutionalization of the mental hospitals and to demonstrate the changes in care for the mentally ill as they were moved into community health centers.
Keywords: Mentally ill--Care--Wisconsin--Evaluation.; Deinstitutionalization--Wisconsin--History.; Deinstitutionalization--Wisconsin--Evaluation.; Community health services--Wisconsin--Evaluation.; Mentally ill--Care--Wisconsin--History.; Community health services--Wisconsin--History.